HUBUNGAN SIKAP DAN KETERSEDIAAN INFORMASI KB TERHADAP PERILAKU PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI WILAYAH KERJA PUSKESMAS BATAKTE - Mili Arthanedi Jumetan; Aysanti Yuliana Paulus; Arman Rifat Lette (Jurnal Maternitas Kebidanan, 2023)
One of the goals of the Sustainable Development Goals (SDGs) is to realize the highest degree of maternal health through various means, one of which is population development and family planning. One of the goals of the family planning program is to prevent pregnancy. The Long-Term Contraceptive Method (MKJP) is an alternative in preventing pregnancy because MKJP has many advantages, both from a program perspective and from a client (user) perspective. The purpose of this study was to determine the relationship between attitudes and availability of family planning information on the behavior of using MKJP. This study used a descriptive analytic method with a cross-sectional design. The population in this study were family planning acceptors in the working area of the Batakte Health Center, Kupang Regency, namely the villages of Oenesu, Lifuleo and Tesabela. The sampling technique is by random sampling with the type of sampling Propotionate stratified random sampling. Primary data was collected using a questionnaire while secondary data was obtained directly from the research location. Data processing was performed using the chi-square test. The results showed that attitudes obtained a p-value of 0.005 and availability of information with a p-value of 0.943. In conclusion, there is a significant relationship between attitudes and behavior in using MKJP, while the availability of information does not have a significant relationship with behavior in using MKJP. Keywords: Attitude, Availability of information, Family planning, MKJP